Перспективи та новації електронної комерції в Україні - Костова, Наталія Іванівна; Костова, Н. І.; Kostova, Nataliia I.; Фалес, Олександра Георгіївна; Фалес, О. Г.; Fales, Oleksandra H. (Одеса, 2019)
Електронна комерція представляє собою середовище, в якому юридична або фізична особа, що знаходиться в будь-якій точці економічної системи, може легко контактувати із мінімальними витратами з будь-якою іншою юридичною або фізичною особою з метою сумісної роботи: торгівлі, обміну ідеями і «ноу-хау» або просто з метою отримання задоволення. І хоча електронна комерція загалом мало чим відрізняється від традиційного бізнесу, вона вимагає від своїх учасників знання спеціальних Інтернет-термінів, оскільки вони слугують підставою для прийняття того чи іншого рішення, пов’язаного із бізнесом. Це пояснюється специфікою підприємницької діяльності в Інтернеті, а саме із прийняттям, переробкою і наданням інформації. Тому для того щоб участь в електронному бізнесі була плідною, необхідно мати не тільки серйозну правову підготовку, а й знання про бізнес в Інтернеті, включаючи знання технічних термінів тощо.

E-commerce is an environment in which a legal entity or an individual located anywhere in the economic system can easily communicate with any other legal entity or individual with the goal of working together: trading, exchanging ideas and know-how or simply enjoyment. And although e-commerce, as a rule, is not very different from traditional business, it requires knowledge of special Internet terms from its participants, since they provide the basis for making a specific decision related to business. This is due to the specifics of business activities on the Internet, namely, the adoption, processing and provision of information. Therefore, for participation in e-business to be fruitful, it is necessary to have not only serious legal training, but also knowledge of business on the Internet, including knowledge of technical terms, knowledge of e-mail programs, understanding the World Wide Web, knowledge of working with newsgroups; knowledge of «its» audience of consumers of products, works (services); conduct research activities of competitors; develop an advertising policy and the like. The intellectual sphere is currently one of the most important resources of any state, determining its scientific, technical and cultural potential; therefore, a whole system was created that regulates legal relations related to the creation, protection and use of intellectual property (including e-commerce). This system is constantly evolving, new intellectual property objects are emerging, national legislation is being improved and developed, and international cooperation is expanding. The problem of international e-commerce plays a significant role in the system of main priorities of the leading countries of the world. It is e-commerce in the era of the information society that occupies a key place in the structure of the new economy. At the expert and political levels, activities aimed at the development of electronic commerce, which is a powerful lever of economic growth, is an important platform for the transition of national economies to a qualitatively new stage of development, focused mainly on high-tech information technologies. Despite the considerable period of time and the number of international legislative acts aimed at regulating legal relations on the Internet, there are a number of scientific and practical issues that have not received adequate legal support. In particular, economic relations deserve the most attention on the Internet (electronic money, trade transactions and financial flows).
Костова Н. І. Перспективи та новації електронної комерції в Україні / Н. І. Костова, О. Г. Фалес // Часопис цивілістики : наук.-практ. журн. / редкол.: С. В. Ківалов (голов. ред.), Є. О. Харитонов (заст. голов. ред.), К. Г. Некіт (відп. секр.) [та ін.]. - Одеса, 2019. – Вип. 32. – С. 44-49.
Keywords: електронна комерція; електронні технології; інтернет-комунікації; електронні комунікації; electronic commerce; electronic technologies; Internet communications; electronic communications; Research Subject Categories::TECHNOLOGY